CO2 CAPTURE FOR FORMIC ACID PHOTOSYNTHESIS USING MEMBRANE REACTOR - Raihan Aziz, Muhammad
Membrane contactor technology has become an effective option for reducing CO2 levels in flue gas. Absorbents containing CO2 can be directly utilized, particularly in the process of photocatalysis. Photocatalysis is an environmentally friendly technology as it only requires photon or light energy as a driving force. One of the valuable products obtained through this process is formic acid. In this study, the synthesis of ZnO and ZnS catalysts was modified using the sol-gel method with varying molar ratios and calcination temperatures, determining the characteristics of the photocatalysts, and assessing catalyst performance using visible light and model flue gas feed. Based on photoreduction tests, it was found that the synthesized ZnO and ZnS catalysts had diffraction patterns matching the standards, with wavelengths reaching 409.19 nm (visible light). The three best catalysts were those with the ZnO molar ratio and calcination temperature of: (1) 1:2, 400°C, (2) 1:2, 500°C, and (3) 1:1, 400°C, yielding formic acid at 118.39, 115.26, and 102.02 mg/L, respectively. Using an LED lamp as a visible light source resulted in the highest formic acid yield of 18.12 ppm after 240 minutes with a catalyst having a ZnO ratio of 1:1 calcined at 400°C. Using a gas feed with 15% vol CO2 produced the highest formic acid yield of 43.21 ppm after 240 minutes.